EVALUASI KONVERSI DAN DISTRIBUSI ENERGI PADA RESEARCH TEST ENGINE TIPE 240PE BERBAHAN BAKAR GASOLINE JENIS PERTALITE - Paloboran, Marthen; Pangruruk , Thesya Atarezcha Pangruruk; Darmawang, Darmawang; Tjandi , Yunus Tjandi; Yasdin , Yasdin; Wabdillah , Wabdillah; Sidin, Udin Sidik; Asmeati , Asmeati (Jurnal Rekayasa Mesin, 2024)
Gasoline fuel is a kind of fossil fuel that is still the primary fuel for vehicles and motorcycles nowadays. Demand for fuel continues to increase from time to time, so an effort is needed to save the use of fuel. This research is intended as an initial study to determine the quantity of heat energy converted and distributed into several engine performance parameters. Furthermore, the results of this study became the basis for the development of similar research to produce high engine performance and low emissions as well as economists by setting combustion parameters. The result shows that only a small portion of the heat generated from pertalite fuel is used as effective power. Most of the heat energy from the fuel is wasted in the environment and distributed into radiant heat, and some of it becomes heat to the exhaust gases and heat to the cooling water.